Rethinking the Importance of Establishing Adequate Relationships Between Teachers/Educators and Students in Order to Achieve the Best Results in Upbringing and Education - Pektor, Leonard; Golubović, Aleksandra (Od filozofije poučevanja do poučevanja filozofije: Festschrift Rudi Kotnik, 2025)
In this paper, we analyse the phenomenon of education and upbringing, with emphasis on the contemporary educational practice, as it was primarily envisioned by John Dewey, but also by Whitehead, Peterson, and Noddings. We will look into what is today thought of as the role of educators and the importance placed on education for achieving the best possible character traits in students/pupils. We begin by analysing the concept of upbringing and education. Then, we give a short historical overview of the philosophy of education. Next, we take a closer look at the role that educators are expected to fulfil in present circumstances. Our aim is to find out what is really meant when we say that the role has changed from that of firm authority to that of facilitators, and to find out which abilities and dispositions should be developed as part of educating students in the best way possible.